Rooting out faulty adsorption models. Comment on ?Magnetic Prussian blue nanoshells are controllable (sic) anchored on the surface of molybdenum disulfide nanosheets for efficient separation of radioactive cesium from water? - Chu K.H.; Hashim M.A.; Hayder G.; Bollinger J.-C. (Elsevier B.V., 2025)
This correspondence critically examines and rectifies modeling deficiencies identified in a recent article published in this journal. Our analysis covers a range of models and issues, including the Temkin isotherm, the Flory?Huggins isotherm, the pseudo-first-order kinetic model, the pseudo-second-order kinetic model, the intraparticle diffusion model, the Elovich kinetic model, and the computation of thermodynamic parameters. The elucidation and correction of these modeling issues contribute to a more accurate and reliable understanding of the studied phenomena, thereby enhancing the scientific rigor of the subject paper. ? 2024 Elsevier B.V.